If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -7)(x + -8)(x + 7) = 0 Reorder the terms: 4(-7 + x)(x + -8)(x + 7) = 0 Reorder the terms: 4(-7 + x)(-8 + x)(x + 7) = 0 Reorder the terms: 4(-7 + x)(-8 + x)(7 + x) = 0 Multiply (-7 + x) * (-8 + x) 4(-7(-8 + x) + x(-8 + x))(7 + x) = 0 4((-8 * -7 + x * -7) + x(-8 + x))(7 + x) = 0 4((56 + -7x) + x(-8 + x))(7 + x) = 0 4(56 + -7x + (-8 * x + x * x))(7 + x) = 0 4(56 + -7x + (-8x + x2))(7 + x) = 0 Combine like terms: -7x + -8x = -15x 4(56 + -15x + x2)(7 + x) = 0 Multiply (56 + -15x + x2) * (7 + x) 4(56(7 + x) + -15x * (7 + x) + x2(7 + x)) = 0 4((7 * 56 + x * 56) + -15x * (7 + x) + x2(7 + x)) = 0 4((392 + 56x) + -15x * (7 + x) + x2(7 + x)) = 0 4(392 + 56x + (7 * -15x + x * -15x) + x2(7 + x)) = 0 4(392 + 56x + (-105x + -15x2) + x2(7 + x)) = 0 4(392 + 56x + -105x + -15x2 + (7 * x2 + x * x2)) = 0 4(392 + 56x + -105x + -15x2 + (7x2 + x3)) = 0 Combine like terms: 56x + -105x = -49x 4(392 + -49x + -15x2 + 7x2 + x3) = 0 Combine like terms: -15x2 + 7x2 = -8x2 4(392 + -49x + -8x2 + x3) = 0 (392 * 4 + -49x * 4 + -8x2 * 4 + x3 * 4) = 0 (1568 + -196x + -32x2 + 4x3) = 0 Solving 1568 + -196x + -32x2 + 4x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4'. 4(392 + -49x + -8x2 + x3) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(392 + -49x + -8x2 + x3)' equal to zero and attempt to solve: Simplifying 392 + -49x + -8x2 + x3 = 0 Solving 392 + -49x + -8x2 + x3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 12+3y-8+4y= | | 0.5x+5.4=8.6 | | 0=x^2+0-67 | | -3(x-3)=21 | | 5p+24.2=28.65 | | x+1.4x=500 | | -x-9=13-3x | | 0.45x+0.6=0.6x | | 4lnx=3 | | (5x+3)=(4x-1) | | (6x)=42 | | -22+5x=-4x+32 | | 9x(-1)-7=x | | -7-5[2x-5(10+6x)]= | | -3-x=-2x+8 | | (-0.75x+6)-(2.5x-1.9)= | | 2(3x+2)=2x+1+x | | 100=v+23 | | 7-3x=-4+13 | | 29z+15z+11z+35z+46z+14z= | | (m-n-1)(m-n+1)= | | 25=5r | | x+x+2=758 | | 42=7t | | 17-x=5+6 | | 5b+4=6b-4 | | 3-6x=4x+0 | | 4(2x)=100 | | 42x-45=-72 | | 5x-1+9x=4x-7 | | (6+3x)=x-18 | | 6n+4=28-11 |